Conservation of Tupistra (Tupistra nutans Wall. ex Lindl and T. wattii (C.B. Clarke) Hook.f.) aids its ecology and ethnobotany in Darla, Chhukha, Bhutan - Mukhia, Prabhat; Joshi, Nabin; Kunwar, Ripu M.; Dhendup, Kuenzang; Lhamo, Yangchen; Choden, Thinley; Joshi, Rajeev; Kutal, Durga (Ethnobotany Research and Applications, 2026)
Background: Tupistra nutans Wall. ex Lindl and T. wattii (C.B. Clarke) Hook.f. are useful species grown wild in Bhutan. Former has now been hailed as a climate-smart species as it grows elsewhere in transition and ruderal areas, needs little effort in cultivation, and has historically been used in rural livelihood. T. nutans have been extensively cultivated, collected, and used to address the current changes, urging timely documentation and conservation. Methods: Ethnomedicinal plants and the ethnobotany and ecology of T. nutans were assessed following interviews with 78 household members inhabiting Darla, Chhukha, Bhutan. Results: A linear relationship was observed between planting space and T. nutans inflorescence per year, as Pearson’s bivariate correlation coefficient showed significant values (r = 0.48, p< 0.012). The species is now increasingly cultivated and sustainably managed in forests, resulting in growing uses for its parts in the household economy and primary health care, and supporting the theory of availability. Almost all parts (inflorescence, leaf, root, seed) of T. nutans are useful for ethnomedicine. A total of 83.33% of the population (n = 65) used T. nutans, followed by 59 used Swertia chirayita (Roxb.) Karsten and Bergenia ciliata (Haw.) Sternb. Conclusions: Use value shows that T. nutans can be used as a source of nutrition and a future constituent of traditional medicine. Continued research on commercial cultivation and sustainable utilization of T. nutans should be sustained, as it is considered a potential climate-smart crop to benefit the larger society. Keywords: Tupistra nutans, ethnomedicinal plant, food, cultivation, climate-smart, Bhutan.